Implementation of the TERPADU Learning Concept during the Covid-19 Pandemic at Integrated Islamic Junior High School - Elbina Mamla Sa'idah; Munzir Hitami; Abu Anwar (STAI Hubbulwathan Duri, 2022)
Integrated Islamic Schools under the auspices of JSIT have an integrated curriculum by combining the national curriculum and JSIT's own curriculum. However, during the Covid-19 Pandemic, limited learning activities caused problems in the process of implementing the TERPADU approach (study, explore, formulate, present, apply, mundane, ukhrowi). This study aims to analyze the implementation of the TERPADU concept at SMPS IT Mutiara Duri. The research method uses a case study at SMPIT Mutiara Duri with data collection techniques involving interviews, documentation and observations. The results of the study revealed that the learning plan and implementation of learning with the TERPADU approach could be implemented well and the teacher had no difficulty in meeting the indicators of success in the subjects being taught.